Experimental and Numerical Analysis of Incompressible Flow over an Iced Airfoil (Journal of Engineering, 2014)
Determining the aerodynamic characteristics of iced airfoil is an important step in aircraft design.  The goal of this work is to study experimentally and numerically an iced airfoil to assess the aerodynamic penalties associated with presence of ice on the airfoil surface. Three iced shapes were tested on NACA 0012 straight wing at zero and non-zero angles of attack, at Reynolds No. equal to (3.36*105). The 2-D steady state continuity and momentum equations have been solved utilizing finite volume method to analyze the turbulent flow over a clean and iced airfoil. The results show that the ice shapes affected the aerodynamic characteristics due to the change in airfoil shape. The experimental results show that the horn iced airfoil consumes more power than the other shapes of ice, its value was (44.4W). The horn iced shape has the worst effect on the airfoil than the other shapes. The present results are compared with previously reported results; it is found there is a very good agreement between them. A comparison between the experimental and computational results of the presented work were pursing the same behavior.